The Influence of Hard Skills, Soft Skills, and Work Experience on Employee Performance (Study at PT Langkat Nusantara Kepong) - Jeremy Silalahi; Feby Aulia Safrin (Indonesian Journal of Advanced Research, 2024)
Employee performance in the workplace is evaluated based on achieving objectives and the level of success an individual attains, with satisfactory performance indicated by goal completion. Various factors within the organization, such as technical abilities, interpersonal skills, and professional background, can influence performance. This research aims to evaluate the individual and collective impacts of technical abilities, interpersonal skills, and professional background on employee performance. The study employed quantitative research methods, focusing on PT Langkat Nusantara Kepong in Padang Brahrang Regency of Langkat, with a sample size of 85 selected through probability sampling. Data were gathered using a Likert scale questionnaire and analyzed through instrument testing, assessment of classical assumptions, multiple linear regression analysis, and hypothesis testing using MS Excel and SPSS version 25. Results indicate that technical abilities, interpersonal skills, and professional background significantly and positively affect employee performance both individually and collectively. The coefficient of determination test reveals a strong correlation between these variables, with an R value of 0.982. Furthermore, the Adjusted R Square value suggests that technical abilities, interpersonal skills, and professional background collectively contribute to 96.4% of employee performance, with the remaining 3.6% attributed to unexamined external factors.